Perancangan Masjid Di Pekanbaru Dengan Pendekatan Arsitektur Futuristik - Alisha Safira Matroni; Muhd Arief Al Husaini; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Pekanbaru City is the capital city of Riau province, where the majority of the population is Muslim. Therefore, the existence of a representative mosque as the main means of worship for Muslims is very necessary. In general, the number of mosques in Pekanbaru City is sufficient, this is proven by the fact that it is not difficult for immigrants to find mosques when they are going to worship. However, the existence of the existing mosque building is still seen as not being able to represent the vision of the city of Pekanbaru